Intimate Partner Violence and Adverse Pregnancy Outcomes - Koirala, S. (Kathmandu University Medical Journal, 2022)
Background Intimate partner violence (IPV) is an abuse or harm that occurs in a close relationship. The World Health Organization (WHO) estimated that, globally, 35% of women living in industrialized and developed countries have experienced exposure to intimate partner violence and during pregnancy it is associated with low birth weight, preterm birth, and even death of the baby.Objective To find out proportion of intimate partner violence and adverse pregnancy outcome among postnatal mothers who recently delivered their baby.Method A cross-sectional study was conducted among 220 postnatal mothers using a structured questionnaire based on 13-item WHO Violence against women instrument in Nepali language. Face-to-face interview technique was used to collect data using consecutive sampling technique at Kathmandu Medical College teaching Hospital. The data were analyzed using SPSS version 20.Result In recent pregnancy, 32.7% of women had experienced intimate partner violence at least once, which has been categorized as physical 28.6%, psychological 30.9%, and 22.7% sexual violence. Among them, 36% had low birth weight babies, 24% had preterm, 2.8% had dead baby, and 35% reported abortion in previous pregnancy. In the binary logistic regression, intimate partner violence was significantly associated with preterm baby (OR-1.143, 95% CI- 0.386-3.384, p=0.002), low-birth weight (OR- 0.237, 95% CI- 0.093-0.602, p ≤ 0.001), and abortion (OR-0.021, 95% CI- 0.003-0.175, p ≤ 0.001).Conclusion One in three women experienced intimate partner violence during their recent pregnancy and is associated with adverse pregnancy outcomes. Programs targeting screening of intimate partner violence against women should therefore be emphasized during reproductive health services such that adverse pregnancy outcomes can be prevented.